Flamboyant shopping center: entre trabalho, lazer e consumo - Almeida, Felipe Mateus de (2016)
In this dissertation, we present a discussion of the relationship between work, leisure and consumption in the capitalist mode of production, and the Shopping Center as a research object. It is a theoretical work of the Marxist perspective to analyze the phenomena of work, leisure and consumption in capitalist society. At first, we present a discussion of the changes in the working world in the light of the theory of accumulation schemes. Then in the second chapter of the dissertation, we make a discussion of work, free time and capitalism, bringing a debate on consumption and leisure, surpassing the functionalist conception and presenting a critical definition of these phenomena. In the third chapter, we dedicated to the study of the Shopping Center, presenting the historical and structural aspects of these developments to then relate this environment with playing and practice of leisure and programmed consumption. With this research, we find that there is no free time in capitalist society, but rather a time increasingly streamlined and practice-oriented consumption and scheduled leisure. We were able to note also that the Shopping Center is one of the main centers of consumption in contemporary society, and an environment where leisure and scheduled consumption are common practices, thanks to the service of marketing, practicality and alleged security Shopping Center offers his regulars. The Shopping Center is a fantasy island in which the individual holds and forget for a minute of things happening out there.